(untitled) (The Macau Ricci Institute Journal, 2023)
On December 17, 2022, the day of his 86th birthday, Pope Francis signed the decree recognizing the heroic virtues of Ricci, making him Venerable. This gives me the occasion for sharing some insights I have gathered from his life. When I joined the Jesuits in France some thirty years ago, I was quite unfamiliar with the story of Matteo Ricci. Now, having lived in China for some twenty years, Ricci has become a real inspiration for me, as he is for many people here, four centuries after his death. I have come to appreciate how important Matteo Ricci still is for many Chinese people, far beyond the small Catholic community in China. Ricci represents a wonderfully positive encounter between China and the West, long before the traumatic experiences of colonisation in the nineteenth and twentieth centuries sullied the relationship. In presenting his life and work, I hope to explain how Ricci found the presence of God, the Chinese Christ, in the people of China.